2020
DOI: 10.1130/ges02152.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons and sediment dispersal in the eastern Midcontinent of North America

Abstract: Results of detrital-zircon analyses (U-Pb ages and initial Hf values, εHft) of Mississippian–Pennsylvanian sandstones in the Michigan, Illinois, and Forest City basins are remarkably similar to data for coeval sandstones in the Appalachian basin, indicating dispersal of sediment from the Appalachian orogen through the Appalachian basin to the eastern Midcontinent during the late Paleozoic. The similarities of results include matches of the two most prominent age groups (1300–950 Ma and 490–350 Ma), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…12E). The detrital-zircon distributions are generally similar to those in the stratigraphically lower Pennsylvanian and Mississippian sandstones in the Forest City basin, which are characteristic of an Appalachian provenance (Kissock et al, 2018;Chapman and Laskowski, 2019;Thomas et al, 2020). In contrast, the Middle Permian Whitehorse sample includes a secondary group with ages of 638-519 Ma and a minor mode of 576 Ma (Fig.…”
Section: Anadarko Basin and Other Intracratonic Basinsmentioning
confidence: 73%
See 2 more Smart Citations
“…12E). The detrital-zircon distributions are generally similar to those in the stratigraphically lower Pennsylvanian and Mississippian sandstones in the Forest City basin, which are characteristic of an Appalachian provenance (Kissock et al, 2018;Chapman and Laskowski, 2019;Thomas et al, 2020). In contrast, the Middle Permian Whitehorse sample includes a secondary group with ages of 638-519 Ma and a minor mode of 576 Ma (Fig.…”
Section: Anadarko Basin and Other Intracratonic Basinsmentioning
confidence: 73%
“…1B and 5; Tables 1 and 2; Supplemental Tables S1 and S2) represent the sedimentary cover over the Wichita and Arbuckle uplifts, in contrast to the conglomerates that rest unconformably on the Precambrian-Cambrian crystalline rocks in the uplifts (Thomas et al, 2016). Published U-Pb and Hf data from a Permian sandstone (Thomas et al, 2020) on the divide between the Anadarko basin and the intracratonic Forest City basin on the north (Figs. 1 and 5B) provide a test of regional dispersal systems.…”
Section: ■ Samples For Detrital-zircon Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This drainage system, with an area of ~900,000 km 2 , represents the main sediment outfall for southern Africa (Bremner et al, 1990). In North America, several detrital-zircon studies have now demonstrated far-flung sediment delivery systems that spanned the entire width of the continent during the peak assembly of the Pangean supercontinent (Pennsylvanian-Permian) (Gehrels et al, 2011;Kissock et al, 2017;Thomas et al, 2020), and the same would remain true for the source-tosink delivery system that would have connected Patagonian source rocks with the Karoo basin during the late Paleozoic (Johnson, 1991;Sato et al, 2015;Gomis-Cartesio et al, 2018).…”
Section: Pilmatué Sands: the End Of A Long-lived Delivery System In Smentioning
confidence: 99%
“…
Detrital geochronology has transformed the way geologists approach many Earth Science questions. Research incorporating detrital geochronology is wide ranging, from standard application in studies of sediment provenance and dispersal patterns (e.g., Thomas et al, 2020), determination of the maximum depositional age of stratigraphy (e.g., Dickinson & Gehrels, 2009; Vermeesch, 2020), and reconstructing paleogeography and landscape evolution (e.g., Roberts, 2012), to recent novel applications in determining controls on paleoclimate modulations (e.g., McKenzie et al, 2016), placing temporal constraints on floral and faunal continental ecosystems (e.g., Tucker et al, 2013), and estimating the age of early hominins (e.g., Böhme et al, 2017).Zircon is the mineral of choice in detrital geochronology as it is physically and chemically robust, refractory, can survive multiple erosional and/or tectonic cycles, and incorporates abundant U with little initial Pb (Cherniak et al, 1997;Speer, 1980;Stacey & Kramers, 1975). In addition to being a useful mineral for geochronology, zircon can also be paired with secondary information such as (U-Th)/He or fission track thermochronometry for determining thermal histories (e.g.
…”
mentioning
confidence: 99%